Quality of nursing care and patient satisfaction in an emergency department at a public hospital in Chiclayo, 2024 - Parraguez Cornetero, Elmer Jesus (2025)
The quality of care is key to assess patient satisfaction; however, there are deficiencies in health centers and hospitals. Therefore, the objective of this article was to determine the relationship between the quality of nursing care and patient satisfaction in an emergency service. Method: quantitative approach study, non-experimental, cross-sectional and correlational design. The population included 500 patients and the sample 217. The survey was used to collect information, applying two validated questionnaires: "Nursing Care Quality Questionnaire" by Marcelo Mallqui and "Patient Satisfaction Questionnaire" SERVQUAL, with Kappa indices of 77.96% and 66.86%, and reliability measured with Cronbach's α of 0.89; 0.84 (expectations) and 0.80 (perception). The information was processed using Excel 2016 and SPSS v27. Spearman's correlation coefficient was applied to evaluate the relationship between variables, and the ethical criteria of the Belmont Report were respected. Main results: There is a weak positive correlation (rho = 0.483) between the variables. 54% of patients considered the quality of care as moderate, and 100% were satisfied in four dimensions of satisfaction, although only 3% expressed dissatisfaction in the empathy dimension. Concluding: The research reveals a weak positive correlation between the variables. Patients value technical competence, but need emotional and human care, highlighting the need to improve empathy and interpersonal communication for comprehensive and satisfactory care.